TAKHRĪJ HADIS TAWĀZUN DAN IMPLEMENTASINYA SEBAGAI NILAI PENDIDIKAN ISLAM DALAM BUKU AL-QUR’AN HADIS KELAS VIII MADRASAH TSANAWIYAH - Anadita Veria Sandi; Romlah Abubakar Askar (UIN Siber Syekh Nurjati Cirebon, 2025)
The principle of tawāzun (balance) in Islam holds a central position as a foundation for character building and education that integrates spiritual aspects with social life. This article examines the hadiths on tawāzun presented in the Al-Qur’an Hadith textbook for Grade VIII of Madrasah Tsanawiyah, published by the Ministry of Religious Affairs of the Republic of Indonesia. The study employs a library research approach with the method of takhrīj al-hadith to trace the chain of transmission (sanad) and the text (matan) of the hadiths used as references. The findings indicate that the tawāzun hadiths in the textbook originate from authoritative hadith collections, particularly Ṣaḥīḥ Muslim and Sunan al-Nasā’ī, and are classified as authentic in terms of both sanad and matan. The content of these hadiths emphasizes the necessity of maintaining balance in life, covering both worship and worldly activities. The Islamic educational values contained therein include moderation, responsibility, harmony between the physical and spiritual, as well as awareness of life’s holistic purpose. Thus, the tawāzun hadiths are highly relevant as a basis for Islamic character education in shaping students’ moderate and balanced attitudes. Prinsip tawāzun (keseimbangan) dalam Islam menempati posisi penting sebagai landasan pembentukan karakter dan pendidikan yang menyatukan aspek spiritual serta sosial kemasyarakatan. Artikel ini mengkaji hadis-hadis tentang tawāzun yang terdapat dalam buku al-Qur’an Hadis kelas VIII Madrasah Tsanawiyah terbitan Kementerian Agama Republik Indonesia. Penelitian ini menggunakan pendekatan kepustakaan dengan metode takhrīj hadis untuk menelusuri sanad dan matan hadis yang dijadikan rujukan. Hasil kajian menunjukkan bahwa hadis-hadis tawāzun dalam buku tersebut bersumber dari kitab-kitab hadis otoritatif, terutama Ṣaḥīḥ Muslim dan Sunan al-Nasā’ī, serta dinilai sahih dari segi sanad dan matannya. Kandungan hadis-hadis tersebut menegaskan pesan penting mengenai keseimbangan hidup dalam aspek ibadah dan aktivitas duniawi. Nilai-nilai pendidikan Islam yang terkandung meliputi moderasi, tanggung jawab, harmoni jasmani dan rohani, serta kesadaran akan tujuan hidup yang holistik. Dengan demikian, hadis tawāzun relevan dijadikan dasar pendidikan karakter Islami dalam membentuk sikap moderat dan seimbang bagi peserta didik.